Decoys as potential therapeutic tools for diabetes. Issue 7 (July 2021) - Mahjoubin-Tehran, Maryam; Rezaei, Samaneh; Atkin, Stephen L.; Montecucco, Fabrizio; Sahebkar, Amirhossein
Highlights: There is an urgent need for novel therapeutic approaches against diabetes. Decoy-based therapy is an emerging strategy that shows promise for diabetes and its complications. Decoy technologies include decoy oligodeoxynucleotides and decoy peptides. This review summarizes the therapeutic effects of decoy-based therapies in diabetes. Abstract : Current therapeutic approaches for diabetes are focused on improving glycemic control to prevent diabetes-related complications, but such approached are not completely successful. Decoy technologies such as decoy oligodeoxynucleotides (ODNs) and decoy peptides have emerged as therapeutic tools in diabetes. Decoy ODNs carry a DNA recognition motif for the binding of transcription factors in order to trap them and block their effects, whereas decoy peptides mimic the binding structure of the receptor protein, bind to the docking site of the target ligand, and prevent the interaction of the ligand and receptor. This review summarizes the technologies that have been developed to date and the studies that have investigated the therapeutic effects of decoy ODNs and peptides in diabetes.